Measuring and Predicting Heterogeneous Recessions - Cem Cakmakli; Richard Paap; Dick van Dijk (Tinbergen Institute, 2011)
This paper conducts an empirical analysis of the heterogeneity of recessions inmonthly U.S. coincident and leading indicator variables. Univariate Markovswitchingmodels indicate that it is appropriate to allow for two distinct recessionregimes, corresponding with `mild' and `severe' recessions. All downturnsstart with a mild decline in the level of economic activity. Contractions thatdevelop into severe recessions mostly correspond with periods of substantialcredit squeezes as suggested by the `financial accelerator' theory. MultivariateMarkov-switching models that allow for phase shifts between the cyclicalregimes of industrial production and the Conference Board Leading EconomicIndex confirm these findings.
urn:NBN:nl:ui:15-1765/26863
Keywords: C11; C32; C51; C52; E32; 330; Business cycle; phase shifts; regime-switching models; Bayesian analysis; Konjunktur; Markovscher Prozess; Bayes-Statistik; Schätzung; USA